Factors influencing seniors' willingness to pay intention for exercise in the civil sports and recreation centers - Fang, Chin-Yi; Chen, Po-Yu; Liao, Yung (Frontiers in Public Health, 2023)
Background The increasing trend for an older population is a phenomenon that is well recognized around the world. The percentage of senior citizens participating in sports, recreation, and leisure activities is also increasing in order to sustain a healthier society. As long as seniors recognize the importance and benefits of keeping healthy, they would prefer to be active in various sports and fitness activities. The seniors could engage in making decisions about their own health by exercising regularly and by encouraging their similar-age peers. The civil sports and recreation centers (CSRCs) in Taiwan have adopted operating transfer (OT) and are located mainly in metropolitan areas, with programs consisting of indoor sports offering people daily exercise. The major aims of the CSRC are to keep the citizens in good health and not to be the city government's financial burden. The extant literature examines the determinants of general consumer behavior, neglecting studies on older adults. This study aims to explore the factors influencing seniors' willingness to pay (WTP) more for exercise in CSRCs outside of free hours. Methods This mixed-method study consists of quantitative and qualitative analyses. For the quantitative component, we invited five experts in the sports industry from the industry and academia to evaluate the validity of the questionnaire. A questionnaire consisting of motivation, exercise involvement, and constraint constructs in the quantitative method was administered to 193 older adults in CSRCs. The collected data were analyzed through descriptive statistics, t-test, one-way analysis of variance (ANOVA), and structural equation model (SEM). Results Empirical results indicate that WTP in groups of people aged 75–79, 70–74, and 65–69 years is higher than in the group of people aged 85 years and above. Exercise involvement and motivation had more of a positive impact on seniors' WTP. Discussions Developing a regular exercise habits and having social interaction in exercise courses drive female seniors to pay more for body health. The results of this study provide managers of CSRCs with decision-making recommendations: (1) initiate entry-level sports courses, such as quick chair exercise, to cultivate among seniors the habit of exercise; (2) motivate seniors to participate in sports with other seniors in order to enhance their social activity and raise their WTP more for sports consumption outside of free scheduled periods; and (3) recruit seniors as exercise coaches or personal trainers to pass their experiences with other people of their age. In addition to expanding seniors' social connections, it encourages peers to exercise. Managerial implications and future research are also discussed. Conclusion This study contributes to exploring the determinants of seniors' WTP intention. Motivation and exercise involvement had a significantly positive impact on seniors' WTP intention.